2005
DOI: 10.1161/01.atv.0000150045.27127.37
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADAMTS-1 in Atherosclerosis

Abstract: Objective-We investigated the potential role of ADAMTS-1 (a disintegrin and metalloprotease with thrombospondin motif type I) in atherogenesis. Methods and Results-ADAMTS-1 is expressed at the highest levels in the aorta when compared with other human tissues examined. Immunolocalization studies in human aorta and coronary artery indicate that ADAMTS-1 expression is mainly seen at low levels in the medial layer, but upregulated in the intima when plaque is present. We found that ADAMTS-1 mRNA levels are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…Five ADAMTS sites have been characterized in the aggrecan core protein (Caterson et al 2000;Lemons et al 2001), two to four in the proteoglycan isoforms of versican (V2-V0) (Jonsson-Rylander et al 2005;Sandy et al 2001;Westling et al 2004) and one in brevican (Matthews et al 2000;Yamada et al 1995). Interestingly, in all of these lecticans one ADAMTS-site is located next to the globular G1-domain allowing the selective release of the large GAG-carrying portions from the complex with hyaluronan and link proteins.…”
Section: Matrix Turnovermentioning
confidence: 99%
“…Five ADAMTS sites have been characterized in the aggrecan core protein (Caterson et al 2000;Lemons et al 2001), two to four in the proteoglycan isoforms of versican (V2-V0) (Jonsson-Rylander et al 2005;Sandy et al 2001;Westling et al 2004) and one in brevican (Matthews et al 2000;Yamada et al 1995). Interestingly, in all of these lecticans one ADAMTS-site is located next to the globular G1-domain allowing the selective release of the large GAG-carrying portions from the complex with hyaluronan and link proteins.…”
Section: Matrix Turnovermentioning
confidence: 99%
“…Plasmin has been shown to degrade native versican in vitro . Finally, ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs)-1 (Sandy et al 2001, Jonsson-Rylander et al 2005, -4 (Sandy et al 2001), -5 (unpublished observations in Cross et al;Cross et al 2005), and -9 (Somerville et al 2003) have been reported to cleave either native versican or versican peptide substrates, whereas ADAMTS-8 and -15 are candidates based on sequence similarity (Nicholson et al 2005). …”
Section: Proteinases Capable Of Cleaving Versicanmentioning
confidence: 99%
“…The 70-kDa G1 fragment of versican formed by ADAMTS activity at the Glu 441 -Ala 442 bond of V1 has been documented (Sandy et al 2001), whereas other potential ADAMTS cleavage sites, such as Tyr 423 -Ile 424 of V1, have been proposed based on activity against peptide substrates (Jonsson-Rylander et al 2005). There is increasing evidence for the role of ADAMTS enzymes in the catabolic modification of versican, but further work is necessary to characterize the complete panel of proteolytic enzymes involved in versican cleavage in vascular tissue and their activation patterns in the various forms and stages of vascular pathologies.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the role of ADAMTS proteases in inflammation and atherosclerosis has come to light [25]. Jonsson-Rylander and colleagues [26] reported that ADAMTS-1 might expedite atherogenesis by cleaving the ECM protein versican. The 227 Pro polymorphism in ADAMTS-1 was associated with a nearly twofold increased risk of coronary heart disease event [27].…”
Section: Discussionmentioning
confidence: 99%